Effect of Fe2O3 on the Crystallization Behavior of Glass-Ceramics Produced from Secondary Nickel Slag - Xiaoming Li; Xuyuan Zang; Xiangdong Xing; Jinke Li; Yuwei Ma; Tao Li (Metals, 2022)
In this paper, glass-ceramics were prepared from secondary nickel slag by the melting method. The effects of Fe2O3 on the crystallization behavior of glass-ceramics were investigated by differential thermal analysis, X-ray diffraction, and scanning electron microscopy. The properties of glass-ceramics such as Vickers hardness, bending strength, and acid and alkali resistance were systematically discussed. The results indicate that the crystallization temperature (Tc) and transition temperature (Tg) of the glass show a trend of decreasing and then increasing with the increase in Fe2O3 content. The precipitation and refinement of the crystalline phase were promoted significantly when the Fe2O3 content was lower (≤9.32 wt%), while the crystallinity decreased slightly when the Fe2O3 content increased to 12.42 wt%. The promotion of crystal precipitation led to the depolymerization of the glass network. When the Fe2O3 content was 9.32 wt%, the sample exhibited the best crystallization ability, consisting of uniformly distributed anorthite, ferrobustamite and glass phases, while the Vickers hardness and bending strength were 11.42 GPa and 121 MPa, respectively.